2014
DOI: 10.1080/09658211.2014.920885
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical reasoning in life narratives buffers the effect of biographical disruptions on the sense of self-continuity

Abstract: Personal identity depends on synchronic coherence and diachronic continuity of the self. Autobiographical remembering and autobiographical knowledge as well as the stability of bodily integrity, of social roles, of significant others and of physical and sociocultural environment have been suggested as supporting a pre-reflective sense of self-continuity. Stark biographical discontinuities or disruptions in these areas may destabilise the sense of self-continuity. To test the hypothesis that autobiographical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 32 publications
5
99
0
3
Order By: Relevance
“…It aligns with the conclusions from recent study that found that among participants who had experienced recent “biographical disruptions” (events which instilled a sense of self-discontinuity), autobiographical reasoning coded in their narratives of key life events was associated with repaired self-continuity (Habermas & Köber, 2014). An analogous effect was not observed in participants who did not experience recent biographical disruptions.…”
Section: Discussionsupporting
confidence: 88%
“…It aligns with the conclusions from recent study that found that among participants who had experienced recent “biographical disruptions” (events which instilled a sense of self-discontinuity), autobiographical reasoning coded in their narratives of key life events was associated with repaired self-continuity (Habermas & Köber, 2014). An analogous effect was not observed in participants who did not experience recent biographical disruptions.…”
Section: Discussionsupporting
confidence: 88%
“…Along with being off-time, certain types of events can be seen as deviations. Positive events are viewed as central to the cultural life script, making negative events (e.g., divorce, illness, losing a job) the deviations [e.g., Grysman et al, 2015;Habermas & Köber, 2015;Rubin & Berntsen, 2003]. Indeed, Habermas [2007] noted that the majority of personal memories in the life story are not a part of the cultural concept of biography, which underscores the difference between the life story and these expectations.…”
Section: Case Examples Of Master Narrativesmentioning
confidence: 99%
“…The expectations for a life can change over time, but these expectations are also relatively intractable -they are rigid and compulsory -which is made vivid when there are deviations from expectations [see Habermas & Köber, 2015]. The challenge of deviation at the individual level can be seen with the stress experienced by those who are off-time with regards to culturally expected normative transitions, such as marriage and childbearing [Elder, 1998;Kaplan & Gangestad, 2005].…”
Section: Case Examples Of Master Narrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the lifespan sample of the Frankfurt longitudinal study MainLife, having experienced changes in life circumstances in the past four years led to a lower sense of self-continuity. Autobiographical reasoning in life narratives, however, compensated for this loss of self-continuity in those who had experienced biographical disruptions [Habermas & Köber, 2015a].…”
Section: Autobiographical Reasoning and Well-being Across Adolescencementioning
confidence: 99%